1999
DOI: 10.1038/sj.bjp.0702515
|View full text |Cite
|
Sign up to set email alerts
|

Gi‐protein α‐subunit mRNA antisense oligonucleotide inhibition of Gi‐coupled receptor contractile activity in the epididymis of the guinea‐pig

Abstract: We have used a reversible permeabilization method to facilitate the entry of Giα1, 2 and 3 G‐protein subunit mRNA antisense or mismatch oligonucleotides into intact tissue, to investigate the G‐protein α‐subunit coupling of α2‐adrenoceptors, neuropeptide Y (NPY) Y1, and A1 adenosine receptors in preparations of the epididymis of the guinea‐pig. The α2‐adrenoceptor agonist, xylazine, elicited concentration dependent contractions from preparations of phenylephrine (3 μM)‐stimulated epididymis (pEC50 value 6.52… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2002
2002
2005
2005

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…99 Previously, we have shown that, in non-prostatic smooth muscle, agents that activate Gi-coupled receptors may not necessarily elicit contractions, but may potentiate the contractile responses to other agents. 23 Thus, cultured cell evidence is quite consistent with the effects of cholinergic agonists in human prostatic tissue and indicates the potential complexity of signalling in the human prostatic stroma. Both oxytocin and vasopressin 42,45 have also been shown to elicit contractions of human prostatic tissues but, as yet, there are no equivalent human cultured prostatic stromal cell data.…”
Section: Cultured Cell Models Of Human Prostate Contractilitysupporting
confidence: 56%
See 1 more Smart Citation
“…99 Previously, we have shown that, in non-prostatic smooth muscle, agents that activate Gi-coupled receptors may not necessarily elicit contractions, but may potentiate the contractile responses to other agents. 23 Thus, cultured cell evidence is quite consistent with the effects of cholinergic agonists in human prostatic tissue and indicates the potential complexity of signalling in the human prostatic stroma. Both oxytocin and vasopressin 42,45 have also been shown to elicit contractions of human prostatic tissues but, as yet, there are no equivalent human cultured prostatic stromal cell data.…”
Section: Cultured Cell Models Of Human Prostate Contractilitysupporting
confidence: 56%
“…20,21 Electrical field stimulation of nerves within human, rat, guinea-pig, rabbit, pig and dog prostate causes contractions that can be abolished by tetrodotoxin, reduced by guanethidine and blocked by ␣ 1 -adrenoceptor antagonists. 19,[21][22][23] These studies indicate that there are similar mechanisms at play in the prostates of all mammalian species and, therefore, that there may be advantages in using animal prostate models to investigate human prostate function. These advantages include the ready availability of animal tissue and the fact that the tissue obtained from laboratory animals is, by nature, very consistent and, in contrast with human tissue obtained at surgery, complete and free from disease.…”
Section: Animal Prostate Models Of Human Prostate Contractilitymentioning
confidence: 99%
“…In particular, NPY exerts a synergistic effect on Gq-mediated NEinduced responses. This raises a question about the molecular mechanisms involved in the potentiating actions of NPY [119,120]. At least three different mechanisms account for the synergistic effects observed in presence of NPY [121].…”
Section: Signalingmentioning
confidence: 99%
“…The endogenous purine adenosine has been shown to play a role in the modulation of various cellular functions including smooth muscle contraction and/or relaxation ( Farmer et al , 1988 ; Haynes et al , 1998a ,1998b; Ford & Broadley, 1999; Haynes et al , 1999 ; Sawmiller et al , 1996 ; Prentice et al , 2002 ; Talukder et al , 2002 ), and K + channel conductance ( Hadjkaddour et al , 1996 ; Gopalakrishnan et al , 1999 ; Haynes, 2000; Marian et al , 2002 ). Although four G‐protein‐coupled adenosine receptors have currently been identified, A 1 , A 2A , A 2B and A 3 ( Fredholm et al , 2000 ; Klotz, 2000; Fredholm et al , 2001 ), the vast majority of functional responses are mediated by the A 1 and A 2A adenosine receptors, coupled to G i and G s , respectively ( Fredholm et al , 2000 ).…”
Section: Introductionmentioning
confidence: 99%